Assessment of weight bias among students and health professionals in medical radiation science. A protocol for a systematic review and meta-analysis - Theresa O’ Donovan; Megan Brydon; Aisling Barry; Mark McEntee (PLoS ONE, 2026)
Weight bias is pervasive in health care, contributing to adverse physical and psychological outcomes for affected individuals. While weight bias has been studied in various healthcare contexts, its presence and impact within medical radiation science remain underexplored. This systematic review aims to synthesise the existing literature on the assessment of weight bias in medical radiation science. This protocol is registered with PROSPERO (CRD42024506662). Comprehensive searches will be conducted across multiple electronic databases using predefined search strategies. Retrieved records will be imported into Covidence for title and abstract screening, followed by full-text review. Two independent reviewers will assess study eligibility and extract data. Methodological quality will be evaluated using a multi-tool appraisal approach tailored to the design of each study. Risk-of-bias will be assessed, and meta-biases will be explored through the inclusion of grey literature. Confidence in the cumulative evidence will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. This systematic review protocol will provide a comprehensive synthesis of the quantitative assessment of weight bias among professionals and students in medical radiation science. By mapping how weight bias is measured, the findings may support awareness-raising efforts and inform development of strategies to reduce weight bias in education and clinical practice. Once complete, the review will be shared internationally via presentations or posters at conferences. It will be published in a peer-reviewed journal.